Implementasi PLTS sebagai Supply Listrik Alternatif pada Fasilitas Masjid Qoryah Thoyyibah Kandang Limun: Implementation of PLTS as an Alternative Electricity Supply at Kandang Limun Qoryah Thoyyibah Mosque Facilities - Handayani, Yanolanda Suzantry; Fitrilina, Fitrilina; Marlina, Neneng Cucu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The Government of the Republic of Indonesia has long encouraged the use of renewable energy, but in fact there are still many people who use primary energy. Seeing this, the idea emerged from the Community Service Team by Bengkulu University lecturers to design and implement Solar Power Plants (PLTS). This renewable energy idea was implemented at the Qoryah Thoyyibah mosque, Kandang Limun Kota Bengkulu. The purpose of this service is the implementation of Appropriate Technology, namely PLTS for alternative energy supply at the Qoryah Thoyibah Mosque facility. So that if there is a power outage by PLN, the facilities at the Qoryah Thoyyibah Mosque can still operate according to their functions. This service method is carried out by two methods, namely counseling and implementation of PLTS Appropriate Technology. It is hoped that in the future by designing and building PLTS as an alternative energy source at the Qoryah Thoyyibah Kandang Limun mosque in Bengkulu City, the backup electricity supply will be fulfilled and we will not always depend on PLN, besides that it can also reduce the monthly cost of electricity at the Qoryah Thoyyibah Mosque. The result of Community Service activities with the 2023 Development scheme is that PLTS has been installed with an AC source to operate lighting lamps with a capacity of 100 WP for PLTS and lamps of 800 Watts. So that it can be operated as a source of lighting for Qoryah Thoyyibah mosque facilities in a state where there is no source from PLN.